Can Political Skill Enhance Business and IT Knowledge?. Issue 2 (3rd April 2017) - Gerow, Jennifer E.; Grover, Varun; Thatcher, Jason Bennett
ABSTRACT: We examine whether Chief Information Officers' (CIOs') political skill enhances their IT and business knowledge as a means of influencing executive teams' commitment to strategic and operational IT initiatives. We empirically examine these relationships using data collected from 139 CIOs. The results suggest CIOs' business and IT knowledge is significantly related to influencing executive team commitment to strategic and operational IT initiatives, but political skill only enhances business knowledge for influencing executive team commitment to operational IT initiatives.